Arbuscular mycorrhizal fungi improve drought toleration in Cinnamomum migao H.W.Li seedlings by increasing plant growth, nutrient uptake and biomass accumulation - Xiao Xuefeng; Tian Xiu; Hao Gang; Xu Lu; Huang Rui; Zan Yue (PLoS ONE, 2026)
Drought stress is a primary factor reducing field crop productivity, and its impact is predicted to intensify and occur more often because of human-influenced environmental and climate changes. Which exerts a critical influence on plant growth and distribution, especially in semi-arid Karst regions including southwest China. Cinnamomum migao H.W.Li ( C. migao ), a tree in the Cinnamomum genus of Lauraceae family, is a medicinally important tree species endemic to southwest China. Arbuscular mycorrhizal fungi (AMF) symbiosis mitigates drought stress in plants, yet the inoculation method affects the establishment and function of this symbiosis remains unclear. Therefore, we conducted an experiment examining the influence of different AMF ( Funneliformis mosseae ( F. mosseae ) and Claroideoglomus etunicatum ( C. etunicatum ) their combination (Mixed)) on C. migao seedlings. AMF colonization rates, root vigor, seedling growth and biomass, soil physicochemical properties, and enzyme activities were measured. The results showed that all three AMF treatments significantly enhanced the growth, plant biomass, and soil enzyme activity of C. migao seedlings. Among them, C. etunicatum demonstrated the most effective overall promotion. Therefore, the application of AMF, particularly C. etunicatum , can enhance the drought resistance of C. migao , which supports its large-scale cultivation and offers insights for ecological restoration in semi-arid regions.